Italy : Financial Sector Assessment Program-Technical Note-Financial Safety Net and Crisis Management Arrangements. (IMF Staff Country Reports; Country Report ;, 2020)
The Italian financial safety net and crisis-management framework has been substantially strengthened since the 2013 FSAP. Among others, the authorities have enhanced the early intervention framework, introduced a new resolution regime (including recovery and resolution planning requirements), and introduced reforms of the two deposit guarantee schemes (DGS) that are active in Italy. Further enhancements at the Banking Union level, as outlined in the 2018 Financial System Stability Assessment for the euro area (IMF Country Report No. 18/226)-including the introduction of an adequately funded common deposit guarantee scheme, a harmonized bank liquidation framework and a finetuning of state aid rules-would yield further benefits for Italy.